AB0104 Develop and Evaluate a New Modified Mankin Score System with Special Attention to Subchondral Bone. (10th June 2014) - He, Y.; Gram, A.; Simonsen, O.; Petersen, K.K.; Karsdal, M.A.; Bay-Jensen, A.-C.
Abstract : Background: The MANKIN score is the most widely used histology evaluation on osteoarthritis (OA). It has been modified in number of studies by different research groups since it was first published 40 years ago. The MANKIN score investigate the degradation level of the articular cartilage by assessing four parameters including: cartilage structure, cellularity, proteoglycan depletion and tidemark integrity. However, it is well-established that the interaction between cartilage and subchondral bone, such as the new vessel invasion from subchondral bone into calcified cartilage and the accompanied nerve formation, play essential role in the onset and progression of OA. Objectives: As to better assess the pathologic changes in joint during OA, we developed a new modified MANKIN scoring system with special attention to the subchondral bone. Methods: Besides 4 categories of evaluation on cartilage, we also performed type X collagen immunohistochemical staining, tartrate-resistant acidic phosphatase (TRAP) staining, cartilage and subchondral bone thickness measurement, the number of vessels counting (CD34), Vascular Endothelial Growth Factor Receptor (VEGFR) immunostaining and nerve growth factor receptor (NGFR, P75staining) immunostaining in 2 areas (lateral femur condyle and lateral tibia plateau) of 11 OA patients undergoing knee replacement surgery at Frederikshavn hospital. Each new evaluation was analyzed the correlation with MANKIN score, of which with moderate correlation would be included into the new scoring table. Furthermore, statistical analysis was performed for inter-/intra- observers variability according to the criteria of new modified scoring system. Results: After carful assessment of the different novel parameters, following were found to be associated with cartilage quality: 1) number of vessels (moderate correlation with MANKIN score, Spearman's r=0.6), 2) number of positive cells expressing NGFR (moderate correlation with MANKIN score, Spearman's r=0.4), and 3) the thickness of cartilage/subchondral bone (moderate correlation with MANKIN score, Spearman's r=0.7). A final scoring scheme was put together (table 1) and tested in 11 patients. The inter-observer variability among two observers for the new score system showed reliability (Person's r=0.80). Repeating scoring by one of two observers showed good reproducibility (Person's r=0.73). Conclusions: The new scoring system was constructed with valuable information to indicate the changes in subchondral bone and the severity of OA, which might be used as a rapid and reliable histology evaluation on both human OA and experiment induced OA animal models. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4224